Analisis Strategi Penguatan Usaha Kecil Menengah Pada Masa Pandemi Covid-19 di Kota Medan - Ngatno Sahputra; Budi Antoro; Zulham Zulham (Universitas Batanghari Jambi, 2021)
It cannot be denied that micro, small and medium enterprises have a strategic role in the country's economic system, among these strategic roles are absorbing local resources and wider employment opportunities and contributing to efforts to alleviate poverty. Based on data from the Ministry of Cooperatives and SMEs of the Republic of Indonesia in 2017, the workforce absorbed from MSMEs was 97.02%. This figure increased from the previous year of 112,828,610 people. The city of Medan has the potential for very rapid economic growth, the Central Statistics Agency (BPS) of Medan noted that the economy of Medan in 2018 grew by 5.92%. Even though the potential of micro-businesses is very potential, various problems still surround micro-businesses, making it difficult to develop. As an economic foundation, the MSME sector is the sector most affected by the Covid-19 outbreak due to the absence of activities outside the home by most people. This study intends to identify and analyze the problems faced by Small and Medium Enterprises and strategies for their strengthening during the Covid 19 Pandemic in Medan City. This research is a qualitative study with a literature review which was conducted in the city of Medan in July-November 2020. The type of data used is secondary data from the Central Statistics Agency and the Ministry of Cooperatives and Small and Medium Enterprises with the object of research being MSME actors. The results showed that the sales of MSME products in the city of Medan decreased by 68% due to difficulty in obtaining raw materials and delays in the distribution process as well as difficulties in capital which resulted in a slowing down of the production process by 16% of the total number of MSMEs in the city of Medan. The strengthening strategy is the Rapid Skimming strategy by setting high sales and promotion prices, or vice versa, namely the Low Skimming strategy and the Rapid Penetration strategy, by setting low product prices and high promotions or vice versa with the Slow Penetration strategy.